Simulasi pada Modifikasi Upper Hose Radiator dengan Pipa Bersirip Menggunakan Software Ansys - Muhammad Riziq Mustofa; Viktor Naubnome; Farradina Choria Suci (Peneliti.net, 2022)
Radiator hoses are generally round and made of polymer rubber. Utilization of this modified hose aims to distribute heat in the coolant to the environment in the hose using a finned pipe so that the heat of the cooling liquid can be wasted with the fins when it is passed, so that when entering the radiator the liquid has a lower temperature. The simulation was carried out using the CAE Ansys Student 2021 R2 software. In this study, water was used as a fluid with an inlet temperature of 360 K, 20 fins, 3 types of fins, namely square, circular, helical and 2 materials, namely aluminum and low carbon steel. The results show that the lowest outlet temperature is in the circular fin with low carbon steel material with a temperature of 348.4 K, and the finned pipe that has a high temperature is the aluminum square fin pipe with a temperature of 359.9 K. There is a change in temperature in each type of fin and material. indicates a decrease in temperature in the flow, this will be very useful and will make the radiator work better because the incoming temperature is lower.